2010
DOI: 10.1016/j.commatsci.2010.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies of staggered Li adatoms on graphene

Abstract: a b s t r a c tWe study Li on graphene using the Vienna ab initio Simulation Package employing the projector-augmented wave method within the generalized gradient approximation for the exchange-correlation potential. We give detailed structural and electronic results for various configurations involving Li on the (1 Â 1), (2 Â 1) and (2 Â 2) two-dimensional unit cells, and we consider the isolated Li dimer on graphene. We consider more detailed configurations than have been studied before, and our results comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
3
23
1
1
Order By: Relevance
“…6,7 Several previous theoretical studies based on first-principles density-functional theory have been performed to provide an atomic level understanding of the interactions between adatoms and graphene. These works focused on the stable configurations of alkali and transition metal adatoms on graphene, [8][9][10][11][12][13][14] charge transfer between graphene and metals, 15 and magnetism. 16 It was found that the adatoms studied from groups I to III of the Periodic Table present ionic bonding, and the adsorption is characterized by minimal change in the graphene electronic states and large charge transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Several previous theoretical studies based on first-principles density-functional theory have been performed to provide an atomic level understanding of the interactions between adatoms and graphene. These works focused on the stable configurations of alkali and transition metal adatoms on graphene, [8][9][10][11][12][13][14] charge transfer between graphene and metals, 15 and magnetism. 16 It was found that the adatoms studied from groups I to III of the Periodic Table present ionic bonding, and the adsorption is characterized by minimal change in the graphene electronic states and large charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we address the particular case of an Li atom interacting with graphene. The stable configuration of Li on graphene has been studied by several previous authors 8,9,14 and it was found for 50% coverage that the hollow site is lower in energy compared to the on-top site by only 0.046 eV (Ref. 14).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] It must be noted that not all foreign atoms open up a bandgap, e.g, the adsorption of lithium atoms makes these structures metallic. [26][27][28][29][30][31] Recently, the use of hydrogen adatoms has been studied and theoretical investigations show that these hydrogenated materials are wide bandgap systems, 13,24,[32][33][34] a result supported by experiment. 25 Although the structural and electronic properties of hydrogenated monolayer and bilayer graphene have been extensively studied, the mechanical response properties of these materials require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…244,246,247 Some initial theoretical studies predicted that a sheet of graphene was able to exceed the maximum theoretical capacity of graphite due to the adsorption of Li atoms to both surfaces of the sheet, allowing a higher Li/C ratio than 1:6. 246,250,252,254 In particular, it has been predicted that a Li 2 C 2 structure was theoretically stable, 250,251 with one Li ion adsorbing atop a carbon atom and another Li ion adsorbing above the C atom on the opposite side of the sheet, with the result of the graphene sheet buckling and forming a structure similar to that of graphane. However, more recent theoretical studies 247,260,261 (supported by Raman spectra that show that the intercalation of Li in few-layer graphene resembles that of graphite 262 ) have suggested that that pristine graphene systems may have a theoretical Li + capacity that is lower than that of graphite.…”
Section: Lithium/alkali Metal Batteriesmentioning
confidence: 99%
“…Taken from Ref. 245 Simulation studies in the area can be largely divided into two sets, MD simulations of electrolytes at graphene (see Section 'Simulations of Electrolytes at Graphene Interfaces'), and DFT calculations investigating the adsorption of the Li + to the graphene electrodes [247][248][249][250][251][252][253][254][255][256][257][258][259] which are discussed below. The maximum Li capacity of graphite is 372 mA h/g, where Li + atoms are adsorbed as LiC 6 in a ( √ 3× √ 3)R30 • structure, with the Li + atoms located in the hollow sites.…”
Section: Lithium/alkali Metal Batteriesmentioning
confidence: 99%